Copper catalyzed reduction of azides with diboron under mild conditions. Issue 14 (2nd April 2020) - Liu, Liwen; Wang, Qianwen; Liu, Yu; Zhang, Xiao; Lu, Da; Deng, Shengqi; Gao, Yihua; Chen, Yang
Graphical abstract: Highlights: A general and practical copper catalyzed reduction of azides with B2 pin2 . Mild reaction conditions, good functional group tolerance, high chemoselectivity. Applicable to sterically hindered azides. Abstract: We report herein the first Cu catalyzed reduction of azides with B2 pin2 (pin = pinacolato) as the reductant under very mild conditions. A series of primary amines and amides were obtained in moderate to excellent yields with high chemoselectivity and good functional group tolerance. This reaction can be performed with a cheap copper salt, a simple NHC ligand and a diboron reagent.